축구 선수의 소셜 미디어 내용 분석을 위한 온톨로지 모형 연구 - 김주학; Joo-hak Kim; 조선미; Sun-mi Cho; 강지연; Ji-yeon Kang (Ch'eyuk kwahak yŏn'gu, 2020)
[목적] 축구와 관련한 소셜 미디어 빅데이터는 축구 선수와 관련된 복합적 차원의 정보를 내포하며 연속적으로 빠르게 생성되고 있다. 이러한 소셜 미디어 내용 분석을 위해 텍스트 마이닝 연구가 활발히 진행되고 있으나 언어의 복잡성과 문맥에 대한 이해, 중의어, 수사어, 신조어 등 언어적 특성으로 다소 제한적으로 분석되는 경향이 있다. 이는 일반적으로 텍스트 마이닝에 사용되는 도구가 분석 주제의 특수성을 배제한 보편적인 용어 사전이나 패키지를 사용하기 때문이라 볼 수 있다. 이 연구는 텍스트 데이터의 의미적 모호성과 용어 간 관계 및 체계를 정의하는 대표적인 도구인 온톨로지(Ontology) 모형을 개발하는 데 그 목적이 있다. [방법] 연구의 목적 달성을 위해, 초기 온톨로지 개발에 유용한 'Ontology Development 101: A Guide to Creating Your First Ontology’의 7단계 개발방법을 적용하였다. 각 7단계는 1)온톨로지 대상 분야와 범위 규정, 2)선행 온톨로지 검토, 3)용어 나열, 4)클래스 정의 및 계층 정의, 5)클래스의 속성 정의, 6)슬롯의 패싯 정의, 7)개별 사례 생성의 단계를 포함한다. 특히, 이 연구의 세 번째 단계인 용어 나열 단계는 온톨로지를 구성하는 핵심 용어를 추출하는 단계인데, 이 연구의 목표가 축구 선수의 소셜 미디어 내용 분석에 활용되는 온톨로지를 개발하는 것이기 때문에 실제 축구 선수와 관련한 소셜 미디어에 등장한 텍스트 분석을 진행하여 484개의 핵심용어를 선정하였다. [결과] 개발한 축구 선수의 소셜 미디어 내용 분석을 위한 온톨로지는 크게 인물, 수행결과, 공통용어, 특정어의 4가지의 영역으로 구성되며 용어의 내용적 특성에 따라 분류되었다. 각 영역에 구성된 484개의 용어에 대하여 관계 및 정의, 속성값을 기술하였다. [결론]개발 온톨로지는 클래스와 객체를 정의하여 용어 간 구분 및 관계를 정의한 객체 지향적 온톨로지 모형이며 축구 선수의 소셜 미디어에서 나타난 지식체계를 대변한다. 또한, 비정형 데이터 분석에 활용될 수 있는 2차 도구로써의 기능을 수행한다. [Purpose] Soccer-related social media BigData includes complex information related to soccer players and is continuously and instantly generated. Text mining research is actively carried out for this kind of social media contents analysis, but it tends to be analyzed with limited linguistic characteristics such as understanding of language complexity and context, ambiguous terms, rhetoric, and new terms. This can be attributed to the fact that the tools commonly used for text mining use universal terminology dictionaries and packages that exclude the peculiarities of the analysis themes. The purpose of this study is to develop an Ontology model, which are representative tools for defining semantic ambiguity and relationships and systems between terms of text data. [Methods] In order to achieve the research objectives, we applied the 7-step development method of ‘Ontology Development 101: A Guide to Creating Your First Ontology’, which is useful for ontology development. Each step includes 1) Determine the domain and scope of the ontology 2) Consider reusing existing ontology 3) Enumerate important terms in the ontology 4) Define the classes and the class hierarchy 5) Define the properties of classes-slots 6) Define the facts of the slots 7) Create instances. In particular, the 3rd-step of this study, the glossary stage, is to extract core terms that make up he ontology, but since the goal of this study is to develop the ontology that can be used in social media contents analysis of soccer players, we conducted a social media text analysis related to actual soccer players and selected 484 core terms. [Results] The ontology which was developed in this research for social media contents analysis of soccer players consisted largely of four parts(General terms, performance results terms, common terms, and Characteristic term) and classified according to the content characteristics of the term. [Conclusion] Developed ontology in this study is object-oriented that defining classes and objects to define divisions and relationships between terms and also means a social media contents knowledge system of soccer players. In addition, it performs a function as a secondary tool which can be utilized for atypical data analysis.